The Level of Verbal Aggression of Children in Relation to the War Exposure of Syria A Field Study Conducted on a Sample of Children both at Home and in Some of the Refuge Accommodation Centers (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
This study aims at identifying the level of the verbal aggression of children both at home and in the refuge accommodation centers during the wartime of Syria. In addition, it investigates the difference between the two genders ,of both samples, in their practicing of verbally aggressive behavior. The researcher has applied the descriptive research method as it conforms to the aim and nature of the research. The research has been conducted in 2017 and the instruments of research have been applied in June, 2017 in Lattakia, Syria. The community of that survey included children brought up both at home and at the refuge accommodation centers ranging from 7 – 10 years old in Lattakia. The sample children were 120 male and female children divided equally in half i.e. 60 children per sample. The refuge accommodation center has been chosen randomly from the accommodation centers of Lattakia like the Stadium Accommodation Center, Harem accommodation center, the Accommodation center of "Jihad Mashi" in addition to some neighborhoods of the afore-mentioned city which serves the purpose of the study. The researcher has developed a research standard to estimate the verbal aggression which conforms to the nature of study and the surrounding conditions. This standard has been later examined and authenticated after being modified. The researcher has attempted to investigate five hypothesis then reached the following conclusions: 1.There is an essential difference in the level of verbal aggression between the two samples; children at home are less verbally aggressive than those at the accommodation centers. 2.There are no statistically significant gender differences between males and females in the use of verbal aggression in the case of the children brought up at home and the children brought up at refuge accommodation centers. 3. There are no statistically significant differences among males in the use of verbal aggression in both samples (the children at home and at refuge accommodation centers.) 4. There is a statistically significant difference among females in the use of verbal aggression in both samples (the children at home and at refuge accommodation centers.)